Strategic planning and individual temporal orientation - Das, T. K. (Strategic Management Journal, 1987)
Abstract This paper examines the role of future orientation of organizational members in the strategic planning enterprise. It explores, conceptually and empirically, the relationship between the future time perspectives of individuals and their preferences for short and long planning horizons. Research with 207 corporate executives confirms the relevance of this individual future orientation. Implications of the temporal perspective for research and managerial practice are discussed.